An Study on Evaporation Residue Excitation Function For 16o+194pt Reaction: Comparative Analysis of ER Excitation Functions in 16O+194Pt Reaction (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In our present estimation, we gauged the ER excitation work for 16O + 194Pt at various research facility shaft energies. Standard measurable model figuring’s utilizing Bohr-Wheeler splitting width under predicted the cross areas, particularly at higher excitation energies. In these counts, the dynamical impacts were excluded. With the presentation of dissemination into our counts, the cross segment expanded with increment in dispersal quality. Kramers' splitting width with dispersal coefficient n = 4 x 10-21 sec-1 repeated the ER cross segment at all energies agreeably. At lower energies, where splitting cross segment is a little division of aggregate combination cross area, the decrease in parting width did not roll out any apparent improvement in ER cross segment. In this area both the counts, accepting Bohr-Wheeler parting width and Kramers' width, yielded tantamount ER cross areas. Re-investigation of frameworks populating the composite frameworks 213,214Fr additionally yielded comparative outcomes.